Computational logistics : 5th International Conference, ICCL 2014, Valparaiso, Chile, September 24-26, 2014. Proceedings - Schulte, Frederik; Voß, Stefan; Ceroni Díaz, Jose A.; Gonzalez-Ramirez, Rosa G. (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 5th International Conference on Computational Logistics, ICCL 2014, held in Valparaiso, Chile, in September 2014. The 11 papers presented in this volume were carefully reviewed and selected for inclusion in the book. They are organized in topical sections entitled: optimization of transport problems; container terminal applications; simulation and environmental sustainability applications.